Physical Activity Level Mapping of Senior High School Students in West Java - Apriantono, Tommy; Herman, Indria; Hasan, Muhamad Fahmi; Juniarsyah, Agung Dwi; Ihsani, Sri Indah; Hidayat, Iwa Ikhwan; Tommy Apriantono; Indria Herman (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2020)
Early physical activity habit plays an important role in building a healthy lifestyle and the degree of fitness in the future. This research was aimed at finding out the level of physical activity of high school students in West Java. The result of the study could be used as a reference and benchmark for policy making in sports. The method used in this study was random sampling, spread in 5 cities / districts in West Java. The data of the level of physical activity were obtained from the IPAQ questionnaire (International Physical Activity Questionnaire). The data of the questionnaire showed that the average level of physical activity was in the high category, with metabolic equivalent values (METs) 1520.80 ± 1444.50. The highest level of physical activity was in Tasikmalaya City, while the lowest was in Kuningan District. However, among the five cities, there was no significant difference. The conclusion is that the physical activity level of West Java high school students is high. However, it should be noted that they also have a fairly high duration of sitting and game playing habits. AbstrakKebiasaan untuk beraktivitas fisik sejak dini berperan penting dalam membangun gaya hidup yang sehat serta derajat kebugaran di kemudian hari. Riset ini berupaya untuk mengetahui sebarapa besar tingkat aktivitas fisik siswa SMA di Jawa Barat, yang pada akhirnya dijadikan acuan dan tolak ukur dalam pembuatan kebijakan dilingkungan olahraga. Metode yang digunakan dalam penelitian ini merupana random sampling, tersebar di 5 kota/kab yang ada di Jawa Barat. Metode penelitian ini menggunakan metode penelitian deskriptif kuantitatif. Data tingkat aktivitas fisik didapatkan dari kuesnioner IPAQ (International Physical Activity Questionnaire). Hasil dari kuesioner tersebut rata-rata tingkat aktivitas fisik dalam kategori tinggi, dengan nilai metabolic equivalent (METs) 3520.2 (±2774.3). Paling tinggi tingkat aktivitas fisik di Kota Tasikmalaya, sedangkan paling rendah ada di Kabupaten Kuningan. Namun dari kelima kota tersebut tidak ada perbedaan yang signifikan. Kesimpulannya kategori tingkat aktivitas fisik siswa SMA Jawa Barat tinggi, namun ada beberapa catatan karena mereka memiliki durasi duduk yang cukup tinggi serta kebiasaan bermain permainan daring yang terlalu sering.